to the discovery learning learning model in physics subjects. the approach used in this study is the quasy experimental method with a qualitative approach with data collection techniques th: Discovery learning hasil belajar - Eni Asrianti Putri; Ovilia Putri Utami Gumay; Ahmad Amin (Irfani, 2026)
This study aims to analyze the responses of teachers and students to the discovery learning learning model in physics subjects. the approach used in this study is the method with a qualitative approach with data collection techniques through interviews with physics teachers and class xi students. the results of the study indicate that teachers still tend to use lecture and discussion methods, and rarely apply discovery learning learning due to limited tools and practical materials in the laboratory. teachers also have not developed the discovery learning learning model, so that learning activities have not fully developed students' scientific skills. from the student's side, most consider physics learning to be less interesting because of the lack of practical and exploratory activities. however, the majority of students show low student physics learning outcomes, so the application of the discovery learning model was chosen because it is considered capable of improving learning outcomes for students of SMA N 4 Lubuklinggau